THE DARK SIDE OF ARTIFICIAL INTELLIGENCE: ANALYSIS OF LONG-TERM SOCIAL CONSEQUENCES AND ETHICAL RISKS - IVANOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper examines the impact of artificial intelligence (AI) on modern society, considering both the positive and negative consequences of its implementation. A comprehensive analysis of publications from scientometric databases such as Google Scholar, Scopus, and Web of Science reveals a trend in AI applications across various fields, ranging from computer science and engineering to education and information technology. The results indicate that most research focuses on the positive aspects of AI adoption, highlighting its benefits and potential advancements. However, beyond its evident contributions to humanity, AI also poses significant negative implications, which are inherently more complex to quantify with concrete data.тThe paper explores social and economic challenges arising from labor market automation, decreasing demand for traditional employment models, and widening digital inequality. Ethical and legal considerations such as algorithmic biases, lack of transparency in decision-making, and privacy concerns due to mass data collection are critically examined. Furthermore, an increasingly dangerous issue is identified: the exponential growth of information and the consequent training of new AI models on publicly available data, which may lead to the propagation of misinformation within AI systems. The author highlights that the openness of data and accessibility of AI model development foster conditions for widespread dissemination of systems that may amplify informational biases and inaccuracies. In this context, the study emphasizes the necessity of interdisciplinary approaches and regulatory mechanisms to minimize adverse outcomes and enhance ethical standards for AI integration in daily life and professional environments. The findings underscore the growing relevance of AI's negative impacts, demanding further academic research and practical solutions, including corporate governance-level interventions.
Keywords: Artificial intelligence; socio-economic impact; ethical challenges; political dynamics; scientometric analysis; educational implications; misinformation